Drosophila ribosomal protein PO contains apurinic/apyrimidinic endonuclease activity. - Yacoub, A (1996)
Drosophila ribosomal protein PO was overexpressed in Escherichia coli to allow for its purification, biochemical characterization and to generate polyclonal antibodies for Western analysis. Biochemical tests were originally performed to see if overexpressed PO contained DNase activity similar to that recently reported for the apurinic/apyrimidinic (AP) lyase activity associated with Drosophila ribosomal protein S3. The overexpressed ribosomal protein was subsequently found to act on AP DNA, producing scissions that were in this case 5' of a baseless site instead of 3', as has been observed for S3. As a means of confirming that the source of AP endonuclease activity was in fact due to PO, glutathione S-transferase (GST) fusions containing a Factor Xa cleavage site between GST and PO were constructed, overexpressed in an E.coli strain defective for the major 5'-acting AP endonucleases and the fusions purified using glutathione-agarose affinity column chromatography. Isolated fractions containing purified GST-PO fusion proteins were subsequently found to have authentic AP endonuclease activity. Moreover, glutathione-agarose was able to deplete AP endonuclease activity from GST-PO fusion protein preparations, whereas the resin was ineffective in lowering DNA repair activity for PO that had been liberated from the fusion construct by Factor Xa cleavage. These results suggested that PO was a multifunctional protein with possible roles in DNA repair beyond its known participation in protein translation. In support of this notion, tests were performed that show that GST-PO, but not GST, was able to rescue an E.coli mutant lacking the major 5'-acting AP endonucleases from sensitivity to an alkylating agent. We furthermore show that GST-PO can be located in both the nucleus and ribosomes. Its nuclear location can be further traced to the nuclear matrix, thus placing PO in a subcellular location where it could act as a DNA repair protein. Other roles beyond DNA repair seem possible, however, since GST-PO also exhibited significant nuclease activity for both single- and double-stranded DNA.